Drosophila lacking microRNA miR-278 are defective in energy homeostasis. - Teleman, A.A.; Cohen, S.M. (Genes & Development, 2006)
The mechanisms that control energy homeostasis and tissue growth during development are closely linked through the insulin signal transduction pathway. Changes in the level of insulin and other hormones reflect the nutritional status of the animal to control circulating sugar levels and fat metabolism. Systemic defects in insulin responsiveness can lead to elevated circulating glucose levels and fat accumulation. Here we present evidence that the microRNA miR-278 plays a role in the control of energy homeostasis in Drosophila. miR-278 mutants have elevated insulin production and are correspondingly lean. Despite the elevated insulin levels, miR-278 mutants have elevated circulating sugar, mobilized from adipose-tissue glycogen stores. We provide evidence that miR-278 mutants are insulin resistant and that miR-278 acts through regulation of the expanded transcript.